Benefits of the Complementary use of Archaeometry Investigations and Historical Research in the Study of Ancient Airplanes: the Breguet Sahara's Rivets. Issue 1656 (22nd August 2014) - Cochard, Audrey; Douin, Joël; Warot-Fonrose, Bénédicte; Huez, Julitte; Robbiola, Luc; Olivier, Jean-Marc; Sciau, Philippe
ABSTRACT: The aim of this paper is to show that historical technical archives and complementary physico-chemical studies can be combined to obtain relevant information on the materials and processes used in the manufacturing of a Breguet 765 Sahara airplane. This will be useful both in history of sciences and technology and in the renovation of this more than fifty years old airplane. The Breguet 765 Sahara plane is the last version of a family of French double-deck transport aircraft produced by Breguet between 1948 and 1960. The gathering of multi-disciplinary information from the literature of the period of production with laboratory investigations has revealed that a "new" aluminum-copper-magnesium alloy was used in the rivets of the Breguet 765. The A-U3G alloy was developed to meet properties requirements of the aeronautical industry for joining sheets of aluminum and was used in the Breguet 765 Sahara to strengthen the joints. Analytical techniques included TEM, EPMA microprobe and metallography.